Al2O3 / PTFE composite microporous membrane as well as preparation method and application thereof
By combining Al2O3 nanoparticles with PTFE resin powder, an Al2O3/PTFE composite microporous membrane was prepared, which solved the shortcomings of existing PTFE microporous membranes in terms of mechanical properties and surface wettability, and realized a proton exchange membrane reinforcement material with high strength, high porosity, large pore size and good surface wettability.
Patent Information
- Application Number
- CN202510109269.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2045-01-23
Smart Images

Figure CN119529453A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polytetrafluoroethylene microporous membranes, and specifically relates to an Al2O3 / PTFE composite microporous membrane and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane is the core material of proton exchange membrane fuel cells. The output power, battery efficiency and production cost of fuel cells are strongly dependent on proton exchange membrane. However, the inherent strength of proton exchange membrane is not high, and the high cost of polymer resin hinders the promotion and performance improvement of proton exchange membrane fuel cells. DuPont and other companies in the United States have successively launched Nafion / PTFE composite reinforced membranes. By using PTFE microporous membrane as a reinforcing material, the mechanical strength of the proton exchange membrane can be effectively improved, and the service life and other properties can be extended. However, higher requirements are placed on the mechanical properties, pore size, porosity and uniformity of PTFE microporous membranes.
[0003] PTFE microporous membranes generally adopt synchronous or asynchronous biaxial stretching process, and form a microporous structure of "fiber-node" staggered arrangement through the entanglement between particles during the stretching process. However, the PTFE microporous membranes prepared by the prior art cannot meet the requirements of reducing the thickness while maintaining high strength and narrow pore size distribution, and cannot be applied to the reinforcing layer of proton exchange membranes. In addition, the surface energy of PTFE itself is low, resulting in poor surface wettability after film formation, and strong anti-adhesion performance is not conducive to the direct infiltration of resin solution. Therefore, it is necessary to improve the preparation process of PTFE porous membranes.
[0004] For example, Chinese patent document CN112827372A discloses that polytetrafluoroethylene resin, extrusion aid, toughening agent and film-forming agent are mixed in proportion, aged at low temperature of 30-60°C, pressed into cylindrical blank, extruded and calendered into sheets, and then stretched in the longitudinal and transverse directions to make high-toughness polytetrafluoroethylene film. Although this modification method can improve the mechanical strength of PTFE microporous membrane, its thickness is large and its surface wettability is poor.
[0005] Chinese patent document CN113413775A adds metal oxide to polytetrafluoroethylene dispersion resin, and the metal element in the metal oxide can destroy the C-F bond in the polytetrafluoroethylene dispersion resin, so that the polytetrafluoroethylene dispersion resin has carbon-carbon double bonds, carbonyl and carboxyl polar groups, which greatly enhances the surface energy of the polytetrafluoroethylene dispersion resin and improves its wettability. In addition, the metal element in the metal oxide and the C element in the polytetrafluoroethylene dispersion resin can form a chemical bond, thereby enhancing the mechanical strength and stability of the material. However, the patent has the following shortcomings: the metal oxide particles in the patent can only be distributed at the position of the node, and the hydrophilic position can only be distributed at the node. It is not conducive to the solution to be infiltrated into the hole when used as a reinforcing material. In addition, the large size will also form a dead point, resulting in the proton channel on both sides of the membrane being cut off and being not conducive to the conduction of the proton. The proton is transmitted to a very important parameter for the proton membrane, which affects the film formation and performance of the proton membrane. The addition of metal oxide to the extrusion aid causes the formed PTFE membrane structure to be uneven, and the dispersion effect of the particles deteriorates. Tween, as a dispersant, has strong hydrophilicity, which can easily lead to an increase in the water content of the mixture. In addition, the solvent has an odor and a high boiling point, which is difficult to remove completely and easily remains in the membrane material. Summary of the invention
[0006] In order to solve the problems in the prior art that a PTFE microporous membrane for proton exchange membrane reinforcement cannot have high mechanical strength, large pore size, small thickness, high porosity and other properties, and that low surface energy leads to poor surface wetting, the present invention provides an Al2O3 / PTFE composite microporous membrane and a preparation method and application thereof.
[0007] In order to achieve the above object, the present invention provides the following technical solutions: An Al2O3 / PTFE composite microporous membrane is composed of Al2O3 nanoparticles and PTFE resin powder, has a porosity of 65%-95%, a thickness of 3-25 μm, an average pore size of 0.10-1.5 μm, a transverse and longitudinal tensile strength of ≥20 MPa, and a water contact angle of ≤90°.
[0008] Preferably, the composite microporous membrane has a porosity of 88% to 90%, a thickness of 5 to 13 μm, an average pore size of 0.30 to 0.40 μm, a strength of ≥25 MPa, a water contact angle of ≤65°, a longitudinal tensile strength of 29 to 40 MPa, and a transverse tensile strength of 27 to 40 MPa.
[0009] Preferably, the Al2O3 nanoparticles in the Al2O3 / PTFE composite microporous membrane account for 1%-15% of the mass of the PTFE resin powder.
[0010] The present invention also provides application of the composite microporous membrane in a proton exchange membrane, especially as a reinforcing material for the proton exchange membrane.
[0011] The present invention also provides a method for preparing the Al2O3 / PTFE composite microporous membrane, comprising the following steps: (1) Preparation of pre-dispersed material: Al2O3 nanoparticles are dispersed in a diffusant and stirred evenly to obtain a pre-dispersed material; (2) Preparation of Al2O3 / PTFE composite base membrane tape: (2.1) Mixing: adding extrusion aid and pre-dispersed material to PTFE dispersed resin powder and mixing evenly; (2.2) Ripening: Place the mixed materials in an environment of 30-60°C for more than 15 hours; (2.3) Prefabrication: The cured material is placed in a mold for pre-pressing to obtain a cylindrical blank; (2.4) Extrusion: The prefabricated cylindrical blank is loaded into an extrusion barrel, and the blank is formed into an extruded sheet with a width of 150-250 mm and a thickness of 1000-2000 μm at 50-70°C using a flat die; (2.5) Calendering: The extruded sheet is pressed into a calendered film strip with a thickness of 300-500 μm under the action of two pressing rollers; (2.6) Degreasing: removing the extrusion aid and the diffusion agent from the calendered film by heat treatment to obtain an Al2O3 / PTFE composite base film tape; (3) Longitudinal stretching and transverse expansion: (3.1) Longitudinal stretching: longitudinally stretching the Al2O3 / PTFE composite base membrane tape to obtain an Al2O3 / PTFE longitudinally stretched tape; (3.2) Transverse expansion: The Al2O3 / PTFE longitudinally stretched tape is transversely expanded, cooled and rolled up at a temperature of 0-10°C to obtain a high-strength Al2O3 / PTFE composite microporous membrane.
[0012] Preferably, the amount of Al2O3 nanoparticles added in step (1) is 1%-15% of the mass of the PTFE resin powder. If the amount added is too little, the strength cannot be improved under the compression ratio conditions of the present invention; if the amount added is too much, the network structure of the final membrane structure may be destroyed, which is not conducive to use as a reinforcing material for the proton membrane, and the reinforcing effect will be weakened.
[0013] The size of Al2O3 nanoparticles is ≤150nm, and the size is further preferably ≤100nm, and further preferably 30-100nm. The Al2O3 nanoparticles are selected from one or more of spherical nanoparticles, nanorods, and nanowhiskers. The size described in the present invention refers to the average value of the particles in the direction of the maximum size, such as the length of round rods, the diameter of spherical nanoparticles, the length of nanorods and nanowhiskers, etc. The present invention disperses the nanoparticles in smaller sizes, and the size of the PTFE primary particles is basically a sphere, a round rod, etc. of about 100-200nm. The present invention will achieve the dispersion of aluminum oxide nanoparticles to the surface of the formed fiber to form a three-dimensional hydrophilic skeleton. It is not simply dispersed to the node structure.
[0014] Preferably, the amount of the diffusing agent added in step (1) is 3-8% of the mass of the PTFE resin powder, preferably 5%. The diffusing agent is selected from one or more of methanol, ether, acetone, toluene, dichloromethane, chloroform, and ethylene glycol tert-butyl ether. Acetone and ether are preferred. When the amount of diffusing agent added is small, the dispersion uniformity is poor, resulting in poor uniformity of film formation; excessive addition will increase the lubricity between PTFE resin particles, change the degree of particle fibrillation during extrusion and calendering, change the fiber structure, and fail to achieve the desired effect.
[0015] Preferably, the PTFE resin powder in step (2.1) has a crystallinity of ≥95% and a relative standard density (SSG) of ≤2.19 g / cm 3 , preferably 2.10-1.19 g / cm 3 .
[0016] Preferably, the amount of the extrusion aid added in step (2.1) is 15-30% of the mass of the PTFE resin powder, and the extrusion aid is one or more of petroleum ether, aviation kerosene, paraffin oil, Isopar M, Isopar L, Isopar V, and Isopar H.
[0017] Preferably, the extrusion compression ratio in step (2.4) is 15-55. When the compression ratio is further increased, although the strength of the film is increased, it will increase the difficulty of subsequent processing and easily lead to uneven subsequent stretching and expansion, thereby reducing the uniformity of the film.
[0018] Preferably, the roller surface temperature of the two pressing rollers in step (2.5) is 50-70°C.
[0019] Preferably, in step (2.6), the heat treatment temperature is 200-250° C., and the heat treatment time is 1-3 min.
[0020] Preferably, the stretching temperature in step (3.1) is 200-250°C, and the longitudinal stretching ratio is 5-15 times.
[0021] Preferably, the lateral expansion process in step (3.2) comprises three parts: a preheating section, an expansion section and a heat setting section. The temperature of the preheating section is 150-250°C, the temperature of the expansion section is 150-250°C, the expansion ratio is 10-20 times, and the temperature of the heat setting section is 320~380°C.
[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses Al2O3 nanoparticles as a modified filler for the PTFE microporous membrane. While utilizing the in-situ enhancement effect of the nanoparticles to improve the mechanical properties of the PTFE microporous membrane, the surface energy of the PTFE microporous membrane skeleton is also improved, giving it good wettability. The reinforcement of the Al2O3 nanoparticles reduces the dependence on a high compression ratio, reduces the difficulty of subsequent processing, and makes it easier to obtain a microporous membrane with high lateral consistency. The optimal mechanical properties, porosity and pore size are obtained by longitudinal and lateral proportional stretching.
[0023] (2) The high-strength Al2O3 / PTFE composite microporous membrane prepared by the preparation method of the present invention has a stable structure, a porosity of 65%~95%, a thickness of 3~15μm, an average pore size of 0.10~1.5μm, preferably 0.2~0.5μm, a transverse and longitudinal tensile strength of ≥20MPa, and a water contact angle of ≤90°.
[0024] (3) The high-strength Al2O3 / PTFE composite microporous membrane preparation method of the present invention is adopted, and a low-boiling point oily solvent is used as a diffusion agent to evenly disperse Al2O3 nanoparticles into PTFE resin powder and an extrusion aid to form a homogeneous mixture, thereby improving the dispersion uniformity of Al2O3 nanoparticles in the PTFE dispersed resin and ensuring the uniformity of the high-strength Al2O3 / PTFE composite microporous membrane. The addition of Al2O3 nanoparticles not only improves the problems of weak strength and low modulus of the PTFE microporous structure, but also improves the surface energy of the PTFE microporous membrane and enhances the interfacial bonding force. In coordination with other processes, the Al2O3 / PTFE composite microporous membrane prepared by this method has high tensile strength, high porosity, small thickness, large pore size and good surface wettability, and the preparation process is simple and easy to promote industrialization.
[0025] (4) The selection of the dispersant and the mixing order of the present invention are conducive to achieving uniform dispersion of the nanoparticles in the PTFE resin powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM image of the high-strength Al2O3 / PTFE composite microporous membrane prepared in Example 1; Figure 2This is a SEM image of the high-strength Al2O3 / PTFE composite microporous membrane prepared in Comparative Example 3; Figure 3 This is a water contact angle diagram of the high-strength Al2O3 / PTFE composite microporous membrane prepared in Example 1; Figure 4 This is a water contact angle diagram of the high-strength Al2O3 / PTFE composite microporous membrane prepared in Example 2; Figure 5 This is a water contact angle diagram of the high-strength Al2O3 / PTFE composite microporous membrane prepared in Example 3; Figure 6 This is a water contact angle diagram of the high-strength Al2O3 / PTFE composite microporous membrane prepared in Example 4; Figure 7 This is a water contact angle diagram of the high-strength Al2O3 / PTFE composite microporous membrane prepared in Comparative Example 1; Figure 8 This is a water contact angle diagram of the high-strength Al2O3 / PTFE composite microporous membrane prepared in Comparative Example 2; Fig. 9 This is a water contact angle diagram of the high-strength Al2O3 / PTFE composite microporous membrane prepared in Comparative Example 3; Fig.10 This is a water contact angle diagram of the high-strength Al2O3 / PTFE composite microporous membrane prepared in Comparative Example 4; Fig.11 This is the water contact angle diagram of the high-strength Al2O3 / PTFE composite microporous membrane prepared in Comparative Example 5. DETAILED DESCRIPTION
[0027] The present invention is further described below in conjunction with the examples and drawings. Unless otherwise specified, the raw materials used in the examples of the present invention are common commercial products. The average particle size of the PTFE dispersed resin powder used is 300-500 μm.
[0028] Example 1 Preparation of high-strength Al2O3 / PTFE composite microporous membrane: (1) Preparation of pre-dispersion liquid: Based on the mass of PTFE resin powder, 15% by mass of Al2O3 nanoparticles (nanowhiskers, average particle size 50 nm) were dispersed in 5% by mass of acetone solution. After mechanical stirring for 0.5 h, a uniform Al2O3 nanoparticle pre-dispersion liquid was obtained.
[0029] (2) Preparation of Al2O3 / PTFE composite base membrane tape: (2.1) Mixing: PTFE dispersed resin powder (SSG is 2.190, crystallinity is 95%) is sieved and loaded into a clean and dry PP sealed barrel, and 15% by mass of Isopar M extrusion aid and dispersed pre-dispersion liquid are added to mix, the total volume does not exceed 2 / 3 of the barrel volume, the mixer speed is 8r / min, and it rotates for 20min to make the PTFE resin powder, extrusion aid and pre-dispersion material fully and evenly mixed, and the mixing environment temperature is 12℃. The use of low boiling point diffusant improves the dispersion uniformity of Al2O3 nanoparticles in PTFE resin powder.
[0030] (2.2) Curing: Transfer the sealed barrel containing the uniformly mixed materials to a 60°C oven and cure for 15 hours to allow the extrusion aid to be fully and evenly coated on the surface of the PTFE resin powder particles.
[0031] (2.3) Prefabrication: The matured PTFE resin mixture is placed in a mold for pre-pressing. The pre-pressing pressure is 2 MPa and the pre-pressing temperature is 25°C. After holding the pressure for 3 minutes, a cylindrical blank is obtained.
[0032] (2.4) Extrusion: The prefabricated cylindrical billet is loaded into the extrusion barrel and extruded through a flat die to obtain an extruded sheet with a width of 250 mm and a thickness of 2000 μm. The die temperature is 70 °C and the extrusion compression ratio is 15.
[0033] (2.5) Calendering: The extruded sheet was pressed into a calendered film strip with a thickness of 500 μm by two pressing rollers, and the roller surface temperature of the two pressing rollers was 70°C.
[0034] (2.6) Degreasing: The calendered membrane strip is placed in a drying oven to remove the extrusion aid and the diffusant to obtain an Al2O3 / PTFE composite base membrane strip. The drying oven temperature is 250°C and the drying time is 1 min.
[0035] (3) Longitudinal stretching and transverse expansion: (3.1) Longitudinal stretching: The Al2O3 / PTFE composite base film tape is longitudinally stretched at a longitudinal stretching temperature of 250°C and a longitudinal stretching ratio of 15 times to obtain an Al2O3 / PTFE longitudinally stretched tape; (3.2) Transverse expansion: The Al2O3 / PTFE longitudinally stretched tape is transversely expanded. The transverse expansion process includes three parts: preheating section, expansion section and heat setting section. The Al2O3 / PTFE longitudinally stretched tape first enters the preheating section at a temperature of 150°C, then enters the expansion section at a temperature of 150°C and an expansion ratio of 10 times, enters the heat setting section at a temperature of 380°C, and finally exits the oven and is rapidly cooled and rolled up at a temperature of 10°C to obtain a high-strength Al2O3 / PTFE composite microporous membrane.
[0036] The high-strength Al2O3 / PTFE composite microporous membrane prepared in Example 1 has a membrane thickness of 12 μm, a porosity of 88%, a pore size of 0.31 μm, a longitudinal tensile strength of 29 MPa, a transverse tensile strength of 27 MPa, and a water contact angle of 45 o . On the premise of ensuring thickness, porosity and pore size, it has the strength and excellent hydrophilicity required for use as a reinforcing material.
[0037] Example 2 Preparation of high-strength Al2O3 / PTFE composite microporous membrane: (1) Preparation of pre-dispersion liquid: Based on the mass of PTFE resin powder, 7% by mass of Al2O3 nanoparticles (nanorods, average particle size 100 nm) were dispersed into 5% by mass of acetone solution, and a uniform Al2O3 nanoparticle pre-dispersion liquid was obtained after mechanical stirring for 0.5 h. (2) Preparation of Al2O3 / PTFE composite base membrane tape: (2.1) Mixing: PTFE dispersed resin powder (SSG is 2.165, crystallinity is 98%) is sieved and loaded into a clean and dry PP sealed barrel, and 22.5% of the mass ratio of Isopar H and the dispersed pre-dispersed liquid are added to mix, and the total volume does not exceed 2 / 3 of the barrel volume. The mixer rotates at 6r / min for 25min to fully and evenly mix the PTFE resin powder, extrusion aid and pre-dispersed material. The mixing environment temperature is 12℃. The use of low boiling point diffusants improves the dispersion uniformity of Al2O3 nanoparticles in PTFE resin powder.
[0038] (2.2) Curing: Transfer the sealed barrel containing the uniformly mixed materials to a 45°C oven and cure for 30 hours to allow the extrusion aid to be fully and evenly coated on the surface of the PTFE resin powder particles.
[0039] (2.3) Prefabrication: The matured PTFE resin mixture is placed in a mold for pre-pressing. The pre-pressing pressure is 2.5 MPa and the pre-pressing temperature is 25°C. After holding the pressure for 2 minutes, a cylindrical blank is obtained.
[0040] (2.4) Extrusion: The prefabricated cylindrical billet is loaded into the extrusion barrel and extruded through a flat die to obtain an extruded sheet with a width of 200 mm and a thickness of 1500 μm. The die temperature is 60 °C and the extrusion compression ratio is 35.
[0041] (2.5) Calendering: The extruded sheet was pressed into a calendered film strip with a thickness of 400 μm by two pressing rollers, and the roller surface temperature of the two pressing rollers was 60°C.
[0042] (2.6) Degreasing: The calendered membrane tape is placed in a drying oven to remove the extrusion aid and the diffusant to obtain an Al2O3 / PTFE composite base membrane tape. The drying oven temperature is 225°C and the drying time is 2 min.
[0043] (3) Longitudinal stretching and transverse expansion: (3.1) Longitudinal stretching: The Al2O3 / PTFE composite base film tape was longitudinally stretched at a temperature of 225°C and a longitudinal stretching ratio of 10 times to obtain an Al2O3 / PTFE longitudinally stretched tape; (3.2) Transverse expansion: The Al2O3 / PTFE longitudinally stretched tape is transversely expanded. The transverse expansion process includes three parts: preheating section, expansion section and heat setting section. The Al2O3 / PTFE longitudinally stretched tape first enters the preheating section at a temperature of 200°C, then enters the expansion section at a temperature of 200°C and an expansion ratio of 15 times, enters the heat setting section at a temperature of 350°C, and finally exits the oven and is rapidly cooled and rolled up at a temperature of 10°C to obtain a high-strength Al2O3 / PTFE composite microporous membrane.
[0044] The high-strength Al2O3 / PTFE composite microporous membrane prepared in Example 2 has a membrane thickness of 10 μm, a porosity of 90%, a pore size of 0.42 μm, a longitudinal tensile strength of 35 MPa, a transverse tensile strength of 38 MPa, and a water contact angle of 49 o .
[0045] Example 3 Preparation of high-strength Al2O3 / PTFE composite microporous membrane: (1) Preparation of pre-dispersion liquid: Based on the mass of PTFE resin powder, 1% by mass of Al2O3 nanoparticles (spherical nanoparticles, particle size 30 nm) were dispersed into 5% by mass of acetone solution and mechanically stirred for 0.5 h to obtain a uniform Al2O3 nanoparticle pre-dispersion liquid; (2) Preparation of Al2O3 / PTFE composite base membrane tape: (2.1) Mixing: PTFE dispersed resin powder (SSG is 2.13, crystallinity is 98%) is sieved and loaded into a clean and dry PP sealed barrel, and paraffin oil with a mass ratio of 30% and dispersed pre-dispersed liquid are added to mix. The total volume does not exceed 2 / 3 of the barrel volume. The mixer rotates at a speed of 4r / min for 30 minutes to fully and evenly mix the PTFE resin powder, extrusion aid and pre-dispersed material. The mixing environment temperature is 12°C. The use of low-boiling point diffusants improves the dispersion uniformity of Al2O3 nanoparticles in PTFE resin powder.
[0046] (2.2) Curing: Transfer the sealed barrel containing the uniformly mixed materials to a 30°C oven and cure for 45 hours to allow the extrusion aid to be fully and evenly coated on the surface of the PTFE resin powder particles.
[0047] (2.3) Prefabrication: The matured PTFE resin mixture is placed in a mold for pre-pressing. The pre-pressing pressure is 3 MPa and the pre-pressing temperature is 25°C. After holding the pressure for 1 minute, a cylindrical blank is obtained.
[0048] (2.4) Extrusion: The prefabricated cylindrical billet was loaded into the extrusion barrel and extruded through a flat die to obtain an extruded sheet with a width of 150 mm and a thickness of 1000 μm. The die temperature was 50 °C and the extrusion compression ratio was 55.
[0049] (2.5) Calendering: The extruded sheet was pressed into a calendered film strip with a thickness of 300 μm by two pressing rollers, and the roller surface temperature of the two pressing rollers was 50°C.
[0050] (2.6) Degreasing: The calendered membrane tape is placed in a drying oven to remove the extrusion aid and the diffusant to obtain an Al2O3 / PTFE composite base membrane tape. The drying oven temperature is 200°C and the drying time is 3 min.
[0051] (3) Longitudinal stretching and transverse expansion: (3.1) Longitudinal stretching: The Al2O3 / PTFE composite base film tape is longitudinally stretched at a temperature of 200°C and a longitudinal stretching ratio of 5 times to obtain an Al2O3 / PTFE longitudinally stretched tape; (3.2) Transverse expansion: The Al2O3 / PTFE longitudinally stretched tape is transversely expanded. The transverse expansion process includes three parts: preheating section, expansion section and heat setting section. The Al2O3 / PTFE longitudinally stretched tape first enters the preheating section at a temperature of 250°C, then enters the expansion section at a temperature of 250°C and an expansion ratio of 20 times, enters the heat setting section at a temperature of 320°C, and finally exits the oven and is rapidly cooled and rolled up at a temperature of 10°C to obtain a high-strength Al2O3 / PTFE composite microporous membrane.
[0052] The high-strength Al2O3 / PTFE composite microporous membrane prepared in Example 3 has a membrane thickness of 5 μm, a porosity of 90%, a pore size of 0.32 μm, a longitudinal tensile strength of 37 MPa, a transverse tensile strength of 39 MPa, and a water contact angle of 65 o .
[0053] Example 4 Preparation of high-strength Al2O3 / PTFE composite microporous membrane: (1) Preparation of pre-dispersion liquid: Based on the mass of PTFE resin powder, 7% by mass of Al2O3 nanoparticles (spherical nanoparticles, particle size 50 nm) were dispersed into 5% by mass of ether solution and mechanically stirred for 0.5 h to obtain a uniform Al2O3 nanoparticle pre-dispersion liquid; (2) Preparation of Al2O3 / PTFE composite base membrane tape: (2.1) Mixing: PTFE dispersed resin powder (SSG is 2.165, crystallinity is 95%) is sieved and loaded into a clean and dry PP sealed barrel, and 30% by mass of extrusion aid paraffin oil and dispersed pre-dispersion liquid are added to mix, and the total volume does not exceed 2 / 3 of the barrel volume. The mixer rotates at 4r / min for 30min to fully and evenly mix the PTFE resin powder, extrusion aid and pre-dispersion material. The mixing environment temperature is 12℃. The use of low boiling point diffusants improves the dispersion uniformity of Al2O3 nanoparticles in PTFE resin powder.
[0054] (2.2) Curing: Transfer the sealed barrel containing the uniformly mixed materials to a 30°C oven and cure for 45 hours to allow the extrusion aid to be fully and evenly coated on the surface of the PTFE resin powder particles.
[0055] (2.3) Prefabrication: The matured PTFE resin mixture is placed in a mold for pre-pressing. The pre-pressing pressure is 3 MPa and the pre-pressing temperature is 25°C. After holding the pressure for 1 minute, a cylindrical blank is obtained.
[0056] (2.4) Extrusion: The prefabricated cylindrical billet was loaded into the extrusion barrel and extruded through a flat die to obtain an extruded sheet with a width of 150 mm and a thickness of 1000 μm. The die temperature was 50 °C and the extrusion compression ratio was 55.
[0057] (2.5) Calendering: The extruded sheet was pressed into a calendered film strip with a thickness of 300 μm by two pressing rollers, and the roller surface temperature of the two pressing rollers was 50°C.
[0058] (2.6) Degreasing: The calendered membrane tape is placed in a drying oven to remove the extrusion aid and the diffusant to obtain an Al2O3 / PTFE composite base membrane tape. The drying oven temperature is 200°C and the drying time is 3 min.
[0059] (3) Longitudinal stretching and transverse expansion: (3.1) Longitudinal stretching: The Al2O3 / PTFE composite base film tape is longitudinally stretched at a temperature of 200°C and a longitudinal stretching ratio of 5 times to obtain an Al2O3 / PTFE longitudinally stretched tape; (3.2) Transverse expansion: The Al2O3 / PTFE longitudinally stretched tape is transversely expanded. The transverse expansion process includes three parts: preheating section, expansion section and heat setting section. The Al2O3 / PTFE longitudinally stretched tape first enters the preheating section at a temperature of 250°C, then enters the expansion section at a temperature of 250°C and an expansion ratio of 20 times, enters the heat setting section at a temperature of 320°C, and finally exits the oven and is rapidly cooled and rolled up at a temperature of 10°C to obtain a high-strength Al2O3 / PTFE composite microporous membrane.
[0060] The high-strength Al2O3 / PTFE composite microporous membrane prepared in Example 4 has a membrane thickness of 11 μm, a porosity of 89%, a pore size of 0.38 μm, a longitudinal tensile strength of 39 MPa, a transverse tensile strength of 40 MPa, and a water contact angle of 52 o .
[0061] Comparative Example 1 The preparation method of the Al2O3 / PTFE composite microporous membrane described in this comparative example 1 is different from that in Example 1 in that the amount of the diffusant added in step (2.4) is 10%. The increase in the amount of diffusant used did not significantly improve the performance of the prepared Al2O3 / PTFE composite microporous membrane, with a membrane thickness of 11 μm, a porosity of 89%, a longitudinal tensile strength of 28 MPa, a transverse tensile strength of 27 MPa, a pore size of 0.33 μm, and a water contact angle of 46°. The use of a diffusant of more than 5% does not further improve the performance of the prepared membrane. If the amount is too much, it will not be conducive to subsequent removal, and it will also cause the particles to be entangled and weakened, which is not conducive to the increase in the number of fibers. Therefore, the amount of diffusant added is preferably 5%.
[0062] Comparative Example 2 The preparation method of the PTFE composite microporous membrane described in this comparative example 2 is different from that of Example 1 in that the amount of Al2O3 nanoparticles added in step (1) is 0. Due to the absence of the addition of Al2O3 nanoparticles, the transverse and longitudinal tensile strengths and surface wettability of the prepared Al2O3 / PTFE composite microporous membrane decreased significantly, with a longitudinal tensile strength of 12MPa, a transverse tensile strength of 15MPa, and a water contact angle of 118°. The remaining parameters did not change much, with a thickness of 13μm, a pore size of 0.28μm, and a porosity of 89%. The present invention uses a dispersant to evenly disperse the Al2O3 nanoparticles, thereby getting rid of the dependence on the compression ratio and other stretching processes, and can obtain high strength and excellent surface wettability while maintaining the uniformity of the membrane.
[0063] Comparative Example 3 The method for preparing the Al2O3 / PTFE composite microporous membrane described in this comparative example 3 is different from that in Example 1 in that the amount of the diffusing agent added in step (1) is 1%. Due to the reduction in the use of the diffusing agent, the dispersion effect of the Al2O3 nanoparticles in the PTFE resin powder becomes poor, resulting in longitudinal and transverse non-uniformity in the surface of the prepared Al2O3 / PTFE composite microporous membrane, and the performance parameters vary greatly, with a membrane thickness of 6 μm, a longitudinal tensile strength of 16 MPa, a transverse tensile strength of 13 MPa, a pore size of 0.68 μm, a porosity of 85%, and a water contact angle of 65°.
[0064] Depend on Figure 1 (Example 1), Figure 2 (Comparative Example 3) It can be seen that the amount of dispersant added can affect the microstructure and performance of the final film. Figure 1 The dispersant is added appropriately, the fiber node structure in the microstructure is uniform, the pore size is small, and Figure 2 The uniformity of the fiber node structure is poor, and the pore structure distribution is large.
[0065] Comparative Example 4 The preparation method of Al2O3 / PTFE composite microporous membrane described in this comparative example 4 is different from that in Example 1 in that the dispersant described in step (1) is ethylene glycol butyl ether EB. The obtained film thickness is 13 μm, the porosity is 76%, the pore size is 0.23 μm, the longitudinal tensile strength is 27 MPa, the transverse tensile strength is 30 MPa, and the water contact angle is 69°. The smaller porosity cannot guarantee the complete infiltration of the proton membrane resin solution, reduces the film formation and conductivity of the proton membrane, and affects its application. The reason is that ethylene glycol butyl ether EB is strongly combined with PTFE and Al2O3 nanoparticles, and it is difficult to completely deviate from it during the degreasing process, resulting in a decrease in the fibrillation degree between PTFE particles during the stretching process and uneven stretching, resulting in an uneven appearance of the prepared Al2O3 / PTFE composite microporous membrane, and a smaller porosity.
[0066] Comparative Example 5 The preparation method of the Al2O3 / PTFE composite microporous membrane described in this comparative example 5 is different from that in Example 1 in that SiO2 nanoparticles are added in step (1) instead of Al2O3. The obtained thickness is 13μm, the porosity is 82%, the pore size is 0.35μm, the longitudinal tensile strength is 26MPa, the transverse tensile strength is 25MPa, and the water contact angle is 119°. After the SiO2 nanoparticles are subjected to high-temperature heat setting during the transverse expansion process, the hydrophilic stability of the particles themselves is weakened, resulting in a smaller decrease in the water contact angle of the prepared PTFE composite microporous membrane.
Claims
1. An Al2O3 / PTFE composite microporous membrane, characterized in that: The Al2O3 / PTFE composite microporous membrane is composed of Al2O3 nanoparticles and PTFE resin powder, has a porosity of 65% to 95%, a thickness of 3 to 25 μm, an average pore size of 0.10 to 1.5 μm, a transverse and longitudinal tensile strength of ≥20 MPa, and a water contact angle of ≤90°.
2. The Al2O3 / PTFE composite microporous membrane according to claim 1, characterized in that: The composite microporous membrane has a porosity of 88% to 90%, a thickness of 5 to 13 μm, an average pore size of 0.30 to 0.40 μm, a strength of ≥25 MPa, a water contact angle of ≤65°, a longitudinal tensile strength of 29 to 40 MPa, and a transverse tensile strength of 27 to 40 MPa.
3. The Al2O3 / PTFE composite microporous membrane according to claim 1, characterized in that: The Al2O3 nanoparticles in the Al2O3 / PTFE composite microporous membrane account for 1%-15% of the mass of the PTFE resin powder.
4. The method for preparing the composite microporous membrane Al2O3 / PTFE composite microporous membrane according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Preparation of pre-dispersed material: Al2O3 nanoparticles are dispersed in a diffusant and stirred evenly to obtain a pre-dispersed material; (2) Preparation of Al2O3 / PTFE composite base membrane tape: (2.1) Mixing: Add extrusion aid and pre-dispersed material to PTFE dispersed resin powder and mix well; (2.2) Ripening: Place the mixed materials in an environment of 30-60°C for 15 hours or more; (2.3) Prefabrication: The cured material is placed in a mold for pre-pressing to obtain a cylindrical blank; (2.4) Extrusion: The prefabricated cylindrical blank is loaded into an extrusion barrel, and the blank is formed into an extruded sheet with a width of 150-250 mm and a thickness of 1000-2000 μm at 50-70° C. using a flat die; (2.5) Calendering: The extruded sheet is pressed into a calendered film strip with a thickness of 300-500 μm under the action of two pressing rollers; (2.6) Degreasing: The calendered film is subjected to heat treatment to remove the extrusion aid and the diffusion agent to obtain an Al2O3 / PTFE composite base film tape; (3) Longitudinal stretching and transverse expansion: (3.1) Longitudinal stretching: The Al2O3 / PTFE composite base membrane tape is longitudinally stretched to obtain an Al2O3 / PTFE longitudinally stretched tape; (3.2) Transverse expansion: The Al2O3 / PTFE longitudinally stretched tape is transversely expanded, cooled and rolled up at a temperature of 0-10°C to obtain a high-strength Al2O3 / PTFE composite microporous membrane.
5. The preparation method according to claim 4, characterized in that: The size of the Al2O3 nanoparticles in step (1) is ≤150nm; the amount of the diffusing agent added is 3-8% of the mass of the PTFE resin powder; the diffusing agent is selected from one or more of methanol, ether, acetone, toluene, dichloromethane, chloroform, and ethylene glycol tert-butyl ether.
6. The preparation method according to claim 4, characterized in that: The PTFE resin powder in step (2.1) has a crystallinity of ≥95% and a relative standard density of ≤2.19 g / cm 3 The amount of the extrusion aid added is 15-30% of the mass of the PTFE resin powder, and the extrusion aid is one or more of petroleum ether, aviation kerosene, paraffin oil, Isopar M, Isopar L, Isopar V, and Isopar H.
7. The preparation method according to claim 4, characterized in that: The extrusion compression ratio in step (2.4) is 15-55; the roller surface temperature of the two pressing rollers in step (2.5) is 50-70°C.
8. The preparation method according to claim 4, characterized in that: In step (2.6), the heat treatment temperature is 200-250°C and the heat treatment time is 1-3 min.
9. The preparation method according to claim 4, characterized in that: The stretching temperature in step (3.1) is 200-250°C, and the longitudinal stretching ratio is 5-15 times; the transverse expansion process in step (3.2) includes three parts: a preheating section, an expansion section, and a heat setting section. The temperature of the preheating section is 150-250°C, the temperature of the expansion section is 150-250°C, the expansion ratio is 10-20 times, and the temperature of the heat setting section is 320~380°C.
10. Use of the composite microporous membrane according to any one of claims 1 to 3 or the composite microporous membrane prepared by the method according to any one of claims 4 to 9 as a reinforcing material for a proton exchange membrane.
Citation Information
Patent Citations
Polytetrafluoroethylene microporous membrane as well as preparation method and application thereof
CN117065583A
Microporous polytetrafluoroethylene (PTFE) bodies with filler
CN1203610A
Diaphragm, electrolytic bath, and method for producing hydrogen
WO2018182006A1
Cited By
Composite proton membrane and preparation method thereof
CN120933410A
Composite proton membrane and method for producing the same
CN120933410B